Design of Web-Based Library Information System On SD Muhammadiyah 4 Surabaya - Pangesti, Esti Vidia; Tanuwijaya, Haryanto; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Muhammadiyah 4 Elementary School Surabaya library need satisfactory service for the convenience of visitors to the library. However, business processes that occur there are still underway manual so that the existing data is not integrated with each other. Additionally librarian often difficulties in data searches both when borrowing, repayment and checking on the sanctions. And also with the members and visitors of the library have difficulty in finding the availability and location of collection.To solve these problems, then created a web-based library design of information systems that integrate existing data so that the information collection can be obtained quickly and accurately. The system is able to improve service in terms of borrowing, repayment, reservation, recommendation and search the collection. It also can accelerate the performance of the library and can provide accurate reports to the librarian.From the implementation of web-based library information system is implemented, it can be concluded that the system can ease the librarian to perform control on borrowing, reservation, booking, recommendation and preparation of reports. Besides members can to search information, booking and nomination of the collection. And based on the results implementation of the system of the questionnaire given to the 5 respondents, indicate that the display system, ease of navigation and precision process assessed either by the user with an average yield of 3.3 sequentially; 2.8 and 3.